Sibling Spillovers and the Choice to Get Vaccinated: Evidence from a Regression Discontinuity Design - Maria Knoth Humlum; Marius Opstrup Morthorst; Peter Rønø Thingholm (Institute of Labor Economics (IZA), 2022)
We investigate the effects of the introduction of a population-wide Human Papillomavirus (HPV) vaccination program on the vaccine take-up of the targeted group of 15-year-old girls and their older sisters. For identification, we rely on a regression discontinuity design and high-quality Danish administrative data to exploit that date of birth determines program eligibility. We find that the program increased the HPV vaccine take-up of both the targeted girls and their older sisters. While the direct effects of the program reduced vaccine-takeup inequality, the spillover effects, in contrast, contributed to an increase in vaccine take-up inequality.
Keywords: I10; I18; I12; I14; 330; health investments; health behavior; peer effects; sibling spillovers; HPV; vaccine; health inequality